Biotin Production and Utilization in a Sewage Treatment Lagoon - Fillipi, Gordon M. (1971)
Biotin, in a sewage oxidation lagoon also receiving potato processing wastes, was observed to increase two logs during the summer period of waste stabilization and then to decline to near earlier concentrations. Three organisms, Aerobacter aerogenes, Chlorella vulgaris, and Thiocapsa floridana, were at least partially responsible for these fluctuations; the latter two organisms were associated with biotin utilization and the former with biotin production. Since copious quantities of biotin are produced in these waste treatment facilities, the vitamin may act as a useful indicator of microbial action on certain organic molecules, especially in domestic and industrial wastes such as those from municipalities and potato and sugar beet processing plants. Furthermore, the presence of biotin in rivers and streams may be indicative of the discharge of incompletely stabilized wastes from these sources.